Physical Performance and Activity in Older Prostate Cancer Survivors in Comparison with Population-based Matched Controls - Reidun Sletten; Marit Slaaen; Line Merethe Oldervoll; Håvard Kjesbu Skjellegrind; Jūratė Šaltytė Benth; Lennart Åstrøm; Øyvind Kirkevold; Sverre Bergh; Bjørn Henning Grønberg; Siri Rostoft; Asta Bye; Paul Jarle Mork; et al. (European Urology Open Science)
Background and objective: Whether radical prostate cancer treatment affects long-term physical performance and physical activity in older men is not known. We aimed to compare physical performance and self-reported physical activity between relapse-free older prostate cancer survivors and population-based controls. Methods: A single-centre, cross-sectional study including 109 men aged ≥70 yr receiving robotic-assisted radical prostatectomy (61.5%) or external beam radiotherapy (38.5%) between 2014 and 2018 was conducted. Population-based matched (age, gender, and education) controls (n = 327) were drawn from the Trøndelag Health Study. The primary (the Short Physical Performance Battery [SPPB] summary score) and secondary (gait speed, grip strength, one-legged balance, and the self-reported Physical Activity Index) outcomes were compared between survivors and controls by adjusted linear mixed models. Key findings and limitations: The SPPB score, gait speed, and Physical Activity Index did not differ between survivors (mean age 78.3 yr, mean time since treatment 52.9 mo) and controls (mean age 78.2 yr). Survivors had slightly poorer grip strength (regression coefficient [RC] –5.81, p < 0.001, 95% confidence interval [CI] –7.46; –4.17) and one-legged balance (RC –4.36, p < 0.001, 95% CI –6.72; –2.00; adjusted models), but the clinical significance is uncertain. Small sample size and potential selection of the fittest survivors are limitations that may reduce the generalisability of our findings. Conclusions and clinical implications: 3 to 8 yr after radical prostate cancer treatment, older men’s overall physical performance and physical activity level were comparable with those of matched controls. This suggests that the treatment had little impact on functional status. Patient summary: In this study, we investigated physical function in older men several years after they had undergone curatively intended treatment for prostate cancer in comparison with men in a general population of the same age and education. We found that physical function was similar, except slightly poorer grip strength and balance on one leg in men treated for prostate cancer. We conclude that the overall physical function was comparable with that of the general population and believe that this indicates that prostate cancer treatment was well tolerated despite older age.